Negotiating Cultural Otherness: Translating the Names of Lithuanian Mythological Household and Water Beings - Gimževskienė, Karolina (Vertimo studijos, 2025)
This article examines the translation of the names of Lithuanian mythological household and water beings into English. It explores how these beings function within mythological tales, what cultural meanings they embody, and the specific challenges their names pose for translators. The study addresses issues related to the choice between domestication and foreignization strategies, with a focus on maintaining the cultural specificity of the source text while ensuring its comprehensibility for English-speaking readers. Employing a comparative cultural approach, the article analyses selected mythological names and proposes possible translation solutions. The discussion is supported by illustrative examples drawn from the English translation of Norbertas Vėlius’ collection of Lithuanian mythological tales.